Effect Of Concentration and Frequency Of Administration Of Guano Fertilizer On The Growth and Production Of Tomato Plants (Solanum lycopersicum var. Cerasiforme) - Andriani Eko Prihatiningrum; Sony Raharjo (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the effect of concentration and frequency of liquid guano fertilizer on the growth and production of tomato (Solanum lycopersicum), conducted in Jiken Village, Tulangan District, Sidoarjo Regency, starting from January to March 2020. This experiment was arranged factorially using Randomized block design data analyzed using ragampa fingerprint at 5% level was repeated 3 times with the first factor, namely the concentration of liquid guano fertilizer consisting of no fertilizer, with a fertilizer concentration of 15ml / plant, with a fertilizer concentration of 20ml / plant, with a fertilizer concentration of 25ml / plants and with a fertilizer concentration of 30 ml / plant. The second factor was the frequency of the interval of guano liquid organic fertilizer, the frequency consisted of giving once a week from 7 DAS to 70 DAS, the frequency was given every 2 weeks from 14 DAS to 70 DAS. The variables observed were plant height, number of leaves, leaf area, stem diameter, number of fruit crops and fruit weight. The results of the study using a 5% variance analysis showed that the frequency of application treatment had a very significant effect on plant height, number of leaves, leaf area and stem diameter. However, there is an interaction between the concentration of liquid guano fertilizer on the number of fruits and fruit weight. The results of this study indicate that the treatment with 30 ml of guano fertilizer with a frequency of 2 weeks gave better growth and tomato production.